The Quality-Adjusted Cyclical Price of Labor - Mark Bils; Marianna Kudlyak; Paulo Lins (Institute of Labor Economics (IZA), 2023)
Typical measures of wages, such as average hourly earnings, fail to capture cyclicality in the effective cost of labor in the presence of (i) cyclical fluctuations in the quality of worker-firm matches, or (ii) wages being smoothed within employment matches. To address both concerns, we estimate cyclicality in labor's user cost exploiting the long-run wage in a match to control for match quality. Using NLSY data for 1980 to 2019, we identify three channels by which hiring in a recession affects user cost: It lowers the new-hire wage; it lowers wages going forward in the match; but it also results in higher subsequent separations. All totaled, we find that labor's user cost is highly procyclical, increasing by more than 4% for a 1 pp decline in the unemployment rate. For large recessions, like the Great Recession, that implies a decline in the price of labor of about 15%.
Keywords: E24; E32; J30; J41; J63; J64; 330; wages; cyclicality; wage rigidity